Adsorption of methylene blue using biochar and magnetic biochar from petai pod: kinetic study in batch and continuous systems - Thevisri Hannanda Rao (2021)
As a treatment process for dye contaminated water, adsorption technique using agroresidues is carried out. The adsorption of methylene blue (MB) from aqueous solutions using biochar and magnetic biochar prepared from Parkia speciosa pod (PSP) or commonly known as petai pod was studied in batch and continuous systems. Biochar was prepared by the carbonisation of PSP waste. Meanwhile, for magnetic biochar, the Parkia speciosa pod was pretreated using iron ions (FeCl3·6H2O). The physical and chemical properties of raw PSP, biochar, and magnetic biochar were characterised using Fourier transform infrared (FTIR) spectroscopy, Brunauer- Emmett-Teller (BET) method, field-emission scanning electron microscopy (FESEM), and X-ray diffraction (XRD). Based on preliminary studies, the carbonisation temperature (800 °C) and adsorbent dosage (1.0 g) were determined. The effect of various initial MB concentrations (25–250 mg/L) on MB removal was examined in batch and continuous adsorption. For batch adsorption, the optimum removal of 99 % was achieved at 25 mg/L of MB using biochar, whereas magnetic biochar was capable of removing approximately 99% of MB at all initial concentrations studied. In continuous adsorption, magnetic biochar recorded a higher saturation rate and adsorption capacity than biochar due to the presence of iron ions and iron oxides, such as Fe3O4 and Fe2O3 on the surface of magnetic biochar, which increased the adsorption capacity of adsorbent. The kinetic data were analysed using the pseudo-first-order, pseudo-second- order, and intraparticle diffusion models. The results showed that the best adsorption of MB was described by the pseudo-first-order model with the correlation coefficient, R2 values of 0.977–0.999 for biochar and 0.904–0.999 for magnetic biochar. Furthermore, the adsorption using magnetic biochar also followed the intraparticle diffusion model at higher initial MB concentrations (> 100 mg/L). Based on the breakthrough curve of MB in the continuous system, biochar showed shorter breakthrough time (50 min) compared to magnetic biochar (930 min). Besides, the continuous adsorption system was evaluated using empirical models (Thomas and Yoon-Nelson) and the results showed that both models represented the adsorption of MB. The desorption rates of spent biochar and magnetic biochar were 80%–99%. The results of this work revealed that the prepared biochar and magnetic biochar demonstrated good performance for the removal of MB in aqueous solutions.